Exploring the interaction mechanism of a dicarboxamide fungicide, iprodione with bovine serum albumin - Tayyab, Saad; Min, Loh Hui; Kabir, Md Zahirul; Kandandapani, Salanee; Ridzwan, Nor Farrah Wahidah; Mohamad, Saharuddin (Springer Verlag, 2019)
Abstract: Binding of iprodione (IPR), a dicarboxamide fungicide, to the carrier protein in bovine circulation, bovine serum albumin (BSA) was characterized with the help of fluorescence, absorption, circular dichroism and Fourier transform infrared (FTIR) spectral measurements in combination with computational analysis. The increase in the KSV (Stern–Volmer constant) value with temperature and absorption spectral results characterized the IPR-induced quenching of BSA fluorescence as dynamic quenching. On the other hand, higher value (> 1011 M−1 s−1) of the bimolecular quenching rate constant (kq) suggested complex formation between IPR and BSA. In view of it, increase in KSV value with temperature can be considered as an indication of the involvement of endothermic apolar (hydrophobic) interactions in stabilizing the IPR–BSA complex, as these forces are maximized at higher temperature. A weak binding affinity was anticipated from the values of the binding constant (Ka = 0.83–2.69 × 103 M−1) for IPR–BSA association. Thermodynamic analysis of the binding data further supported contribution of hydrophobic interactions in the IPR–BSA association process. This result was validated by the computational docking analysis. Spectral results from three-dimensional fluorescence and circular dichroism demonstrated microenvironmental changes around BSA fluorophores and protein’s structural (secondary and tertiary) alterations, respectively, upon IPR binding to the protein. Slight variation in the secondary structures of BSA in the presence of IPR was also verified from FTIR spectral results. IPR was found to bind to both site I (subdomain IIA) and site II (subdomain IIIA) of BSA, showing more preference toward site II, as identified by the competitive drug displacement results and supported by the computational analysis. Graphic abstract: [Figure not available: see fulltext.]. © 2019, Institute of Chemistry, Slovak Academy of Sciences.